The Story of the Markham Car Collection: A Cross-Platform Panoramic Tour of Contested Heritage - Joseph, Pauline; Champion, Erik; Dawson, Beata (Rowman & Littlefield, 2019)
In this article, we share our experiences of using digital technologies and various media to present historical narratives of a museum object collection aiming to provide an engaging experience on multiple platforms. Based on P. Joseph’s article, Dawson presented multiple interpretations and historical views of the Markham car collection across various platforms using multimedia resources. Through her creative production, she explored how to use cylindrical panoramas and rich media to offer new ways of telling the controversial story of the contested heritage of a museum’s veteran and vintage car collection. The production’s usability was investigated involving five experts before it was published online and the general users’ experience was investigated. In this article, we present an important component of findings which indicates that virtual panorama tours featuring multimedia elements could be successful in attracting new audiences and that using this type of storytelling technique can be effective in the museum sector. The storyteller panorama tour presented here may stimulate GLAM (galleries, libraries, archives, and museums) professionals to think of new approaches, implement new strategies or services to engage their audiences more effectively. The research may ameliorate the education of future professionals as well.